Copper-catalyzed cascade annulation of unsaturated α-bromocarbonyls with enynals: a facile access to ketones from aldehydes. Issue 7 (16th March 2016) - Che, Chao; Huang, Qianwen; Zheng, Hanliang; Zhu, Gangguo
Abstract : A Cu-catalyzed cascade annulation of enynals with alkenyl or alkynyl α-bromocarbonyls for the synthesis of various cyclohexenone-fused polycyclic compounds is described. Abstract : A Cu-catalyzed cascade annulation of enynals with alkenyl or alkynyl α-bromocarbonyls for the synthesis of various cyclohexenone-fused polycyclic compounds is described. Up to six new C–C bonds and four new carbocycles can be established in a single reaction, highlighting the high efficiency and step-economics of this protocol. This reaction offers a novel and straightforward entry to the synthesis of ketones featuring the addition of carbon radicals to aldehydes.